Una especie nueva de rana Pristimantis (Amphibia: Strabomantidae) de ojos rojos de la Cordillera de Cóndor, Ecuador - Brito, Jorge (2018)
A new species of medium-sized terrestrial frog of the genus Pristimantis (SVL female 31.5 mm, male 26.9 mm) is described from the montane forest of the Cordillera del Cóndor, southeastern Ecuador from an elevation of 2100 m. We assign provisionally Pristimantis barrigai sp. nov., to the Pristimantis ridens group. The new species differs from other congeners by a distinctive combination of characters: dorsum olive to olive-brown, small tympanum, venter blackish, iris spectral-red, pedal supernumerary tubercles enlarged and numerous and distribution on a sandstone plateau in the cordillera del Cóndor.